4CaaSt: Comprehensive Management of Cloud Services through a PaaS - Garcia-Gomez, Sergio; Escriche-Vicente, Manuel; Arozarena-Llopis, Pablo; Jimenez-Ganan, Miguel; Lelli, Francesco; Taher, Yehia; Biro, Jozsef; Momm, Christof; Spriestersbach, Axel; Vogel, Jurgen; Le Jeune, Goulven; Giessmann, Andrea; et al. (2012 IEEE 10th International Symposium on Parallel and Distributed Processing with Applications, 2012)
The 4CaaSt project aims at developing a PaaS framework that enables flexible definition, marketing, deployment and management of Cloud-based services and applications. The major innovations proposed by 4CaaSt are the blueprint and its lifecycle management, a one stop shop for Cloud services and a PaaS level resource management featuring elasticity. 4CaaSt also provides a portfolio of ready to use Cloud native services and Cloud-aware immigrant technologies.